Control Oriented Model for Diesel Oxidation Catalyst Diagnosis. Issue 15 (2015) - Guardiola, C.; Pla, B.; Mora, J.; Lefebvre, D.
Abstract: On-board diagnosis of the after-treatment system is forced by regulation; with diagnosis limits approaching certification values, a tight surveillance of the after-treatment performance is to be done. This paper presents a simple model for a diesel oxidation catalyst, representing both the thermal and chemical behaviour of the system. In addition to the model description, the paper provides hints on the model fitting process and illustrates its performance in several driving conditions. Despite its simplicity, the model allows a proper description of the exhaust temperature variation, allowing the implementation of several model based diagnostic techniques.